Surface Polarity Regulation by Relieving Fermi‐Level Pinning with Naphthalocyanine Tetraimides toward Efficient Perovskite Solar Cells with Improved Photostability. Issue 27 (7th June 2022) - Zhou, Qin; Cai, Chunsheng; Xiong, Qin; Zhang, Zilong; Xu, Jianbin; Liang, Lusheng; Wang, Shibo; Sun, Weihai; Yuan, Zhongyi; Gao, Peng
Abstract: In perovskite solar cells (PSCs), defective perovskite grain boundaries (GBs) and/or surface due to photo‐excitation and the resulted suboptimal carrier dynamics at the perovskite/charge transport layer, have largely limited further performance enhancement and aggravated the PSCs instability. Fundamentally preventing the formation of these trap‐states through a simple and efficient approach is thus critical to the enhancement of both device performance and stability. Herein, a novel semiconductive silicon naphthalocyanine derivative (Cl‐SiNcTI) to reduce the deep level trap states at the GBs and the surface of perovskite film is successfully employed via a newly proposed photon‐relaxation mechanism. The resulting benign p‐type surface polarity and suppressed non‐radiation recombination lead to improved charge transport in bulk perovskite and at the perovskite/spiro‐OMeTAD interface. With a synergistic contribution of the Cl‐SiNcTI and 2‐(2‐Fluorophenyl)ethylamine iodide (oFPEAI), a 24.30% efficiency is achieved in a single cell with excellent operational stability. Moreover, under steady‐state light illumination, 93% power output compared to its initial state can still be maintained after 250 h of continuous operation. Abstract : A novel energy passivation strategy to reduce the deep level trap states and regulate the surface polarity of polycrystalline perovskite film is exploited by suppressing Fermi‐level pinning via a newly proposed photon‐relaxation mechanism. As a result, 24.30% efficiency is achieved for the perovskite solar cell with excellent light and oxygen stability.